PENGARUH DEBT TO EQUITY RATIO (DER) DAN NON PERFORMING LOAN (NPL) TERHADAP HARGA SAHAM PADA PT. BANK MANDIRI, TBK - Handayani, Anggi Putri; Huda, Nurul (Universitas Riau Kepulauan, 2024)
Stock Price will follow company performance or reflect the value of a company. There are several ways to assess stock price, specifically, the assessment of share prices can be done using a financial ratio analysis model. The purpose of this research is to determine the effect of Debt To Equity Ratio (DER) and Non-Performing Loans (NPL) on stock price at PT. Bank Mandiri, Tbk. The research instrument used is a list of tables containing data on total debt, total equity, total non-performing loans and stock price at PT. Bank Mandiri, Tbk for 10 years, namely from 2013 to 2022. The population of this research is all financial reports of PT. Bank Mandiri, Tbk has been listed on the IDX from 1998 to 2022, which is 24 years. The sample in this research is the financial report of PT. Bank Mandiri, Tbk for 10 years, namely from 2013 to 2022. The sampling technique used in this research was purposive sampling. Research data was collected by means of documentation and literature study and then analyzed by hypothesis testing, t test and f test. The research results show that Debt to Equity Ratio (DER) and Non-Performing Loans (NPL) simultaneously have a significant effect on stock price at PT. Bank Mandiri, Tbk with an F-calculated value of 5.851 with an F-table value of 4.07.